A longitudinal analysis of motivation profiles at work - Howard, Joshua L; Morin, Alexandre JS; Gagné, Marylène (Springer Nature, 2021)
This paper examines the multidimensional nature of workplace motivation and the importance of a continuum structure in self-determination theory through application of complementary variable- and person-centered approaches. This approach is taken to simultaneously model the complexity of motivation and highlight interactions between motivational factors. Additionally, this study represents an initial test of the temporal stability of work motivation profiles. A sample of 510 full-time employees were recruited from a range of occupations. Results support the central importance of a general factor representing self-determination as the most influential factor in an employee’s motivation profile. However, smaller effects associated with the motivation subscales, especially identified regulation, were also noticed. Importantly, motivation profiles were found to be highly stable over the 4-month duration of this study. Results lend support to the theoretical position that while general self-determination is an essential component of motivation, it alone does not fully describe an employee’s motivation.